Neglected immunoregulation: M2 polarization of macrophages triggered by low‐dose irradiation plays an important role in bone regeneration. Issue 8 (16th March 2023) - Chen, Shaoqing; Ni, Su; Liu, Chun; He, Mu; Pan, Yiwen; Cui, Pengfei; Wang, Cheng; Ni, Xinye
Abstract: Current studies have found that low‐dose irradiation (IR) can promote bone regeneration. However, mechanism studies of IR‐triggered bone regeneration mainly focus on the effects of osteoblasts, neglecting the role of the surrounding immune microenvironment. Here in this study, in vitro proliferation experiments showed that low‐dose IR ≤2 Gy could promote the proliferation of bone marrow mesenchymal stem cells (BMSCs), and qRT‐PCR assay showed that low‐dose IR ≤2 Gy could exert the M2 polarization of Raw264.7 cells, while IR >2 Gy inhibited BMSC proliferation and triggered M1 polarization in Raw264.7 cells. The ALP and mineralized nodules staining showed that low‐dose IR ≤2 Gy not only promoted osteoblast mineralization through IR‐triggered osteoblast proliferation but also through M2 polarization of Raw264.7 cells, while high‐dose IR >2 Gy had the opposite effect. The co‐incubation of BMSC with low‐dose IR irradiated Raw264.7 cell supernatants increased the mRNA expression of BMP‐2 and Osx. The rat cranial defects model revealed that low‐dose IR ≤2 Gy gradually promoted bone regeneration, while high‐dose IR >2 Gy inhibited bone regeneration. Detection of macrophage polarity in peripheral blood samples showed that low‐dose IR ≤2 Gy increased the expression of CD206 and CD163, but decreased the expression of CD86 and CD80 in macrophages, which indicated M2 polarization of macrophages in vivo, while high‐dose IR had the opposite effect. Our finding innovatively revealed that low‐dose IR ≤2 Gy promotes bone regeneration not only by directly promoting the proliferation of osteoblasts but also by triggering M2 polarization of macrophages, which provided a new perspective for immune mechanism study in the treatment of bone defects with low‐dose IR.